2006
DOI: 10.2987/8756-971x(2006)22[306:feodrc]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluation of Deet, Repel Care®, and Three Plant-Based Essential Oil Repellents Against Mosquitoes, Black Flies (Diptera: Simuliidae), and Land Leeches (Arhynchobdellida: Haemadipsidae) in Thailand

Abstract: Diethyl methyl benzamide, or deet, a commercial plant-based repellent (Repel Care), and essential ils from 3 species of plants (finger root rhizomes, guava leaves, and turmeric rhizomes), steam distillated and formulated as insect repellents, were evaluated in the field on human volunteers against hematophagous mosquitoes, black flies, and land leeches in Thailand. Field trials were conducted against wild mosquitoes in Bang Bua Thong District, Nonthaburi Province, and in the Thap Lan National Park Headquarters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 11 publications
1
38
0
Order By: Relevance
“…Especially, plant essential oils have been proposed for mosquito control and repelling (Boschitz and Grunewald 1994, Amer and Mehlhorn 2006, Tawatsin et al 2006a, 2006b. In addition, a recent study suggested the use of chitosan-based elicitors for the induction of insect-repelling activity (Wongchai et al 2013).…”
Section: Quantification Of Plant-arthropod Interactions and Disease Vmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, plant essential oils have been proposed for mosquito control and repelling (Boschitz and Grunewald 1994, Amer and Mehlhorn 2006, Tawatsin et al 2006a, 2006b. In addition, a recent study suggested the use of chitosan-based elicitors for the induction of insect-repelling activity (Wongchai et al 2013).…”
Section: Quantification Of Plant-arthropod Interactions and Disease Vmentioning
confidence: 99%
“…Therefore, new repellents would be helpful. Notably, plant seed kernel extracts and essential oils have been proposed for mosquito control and repelling (Boschitz and Grunewald 1994, Amer and Mehlhorn 2006, Tawatsin et al 2006a, 2006b. Testing plant materials, we searched for an assay with simple generally available equipment and potential of automation.…”
Section: Introductionmentioning
confidence: 99%
“…In Thailand, essential oils extracted from B. rotunda , P. guajava , and C. longa and one commercial plant-based repellent (containing turmeric oil 5 % and eucalyptus oil 4.5 %) were tested on human volunteers against blackfl ies ( S. nigrogilvum 99 % of the fl ies collected). All four plant-based repellents gave 100 % protection from the bites of blackfl ies for 9 h, protection decreasing to 93 and 90 % after 10 and 11 h of application of the repellents (Tawatsin et al 2006b ). The extent and duration of protection was the same for deet and the plant products.…”
Section: Blackfl Iesmentioning
confidence: 88%
“…aegypti and Ae. albopictus ) mosquitoes (Tawatsin et al 2006b ). The four plant oils, fi ngerroot, Boesenbergia rotunda (10 %); guava, P. guajava (10 %); turmeric, C. longa (10 %); and a commercial product Repel Care 9.5 % (turmeric oil 5 % and E. citriodora oil 4.5 %), were compared with deet.…”
Section: Repellentsmentioning
confidence: 99%
See 1 more Smart Citation